2014
DOI: 10.5021/ad.2014.26.1.66
|View full text |Cite
|
Sign up to set email alerts
|

An Educational Program That Contributes to Improved Patient and Parental Understanding of Atopic Dermatitis

Abstract: BackgroundProviding an educational program as part of a health care program for the management of atopic dermatitis (AD) patients has rapidly become popular. AD educational programs can be of benefit in measured outcomes for both dermatology specialists and patients.ObjectiveTo determine the effects of programmed education delivered by dermatology specialists on the management and knowledge of AD, we assessed the effectiveness of patient/parental education at improving AD knowledge, and determined the usefulne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 23 publications
(27 reference statements)
1
16
0
2
Order By: Relevance
“…The patients' view supports this implicitly as patients strongly agreed that during the consultation, there was enough time to ask questions and that the physician took enough time to explain the condition to the patient. Our results therefore match to reported study results that (standardized) patient education programmes, for example, in asthma or atopic dermatitis can lead to increased therapy adherence and improved outcomes and/or quality of life …”
Section: Discussionsupporting
confidence: 91%
“…The patients' view supports this implicitly as patients strongly agreed that during the consultation, there was enough time to ask questions and that the physician took enough time to explain the condition to the patient. Our results therefore match to reported study results that (standardized) patient education programmes, for example, in asthma or atopic dermatitis can lead to increased therapy adherence and improved outcomes and/or quality of life …”
Section: Discussionsupporting
confidence: 91%
“…, 17 In a study conducted in Italy, there was a high and significant correlation between the quality of life of children in the age group of 1-12 years and their guardians 23 . This shows that the higher the score of CDLQI, the higher the DFI.…”
Section: Discussionmentioning
confidence: 95%
“…Education plays a vital role in AD management given its chronicity and treatment complexity . Shin et al showed that knowledge scores of caregivers who received a structured educational program were significantly higher than those who did not . Similarly, Gradwell C et al demonstrated that further explanation by a dermatology specialist nurse improved patients’ understanding on treatment duration and means for further support .…”
Section: Discussionmentioning
confidence: 99%